Proteoglycan 4 (lubricin) is a highly sialylated glycoprotein associated with cardiac valve damage in animal models of infective endocarditis. (25th August 2021) - Solakyildirim, Kemal; Li, Yi; Bayer, Arnold S; Sullam, Paul M; Xiong, Yan Q; Lebrilla, Carlito B; Bensing, Barbara A
Abstract: Streptococcus gordonii and Streptococcus sanguinis are primary colonizers of tooth surfaces and are generally associated with oral health, but can also cause infective endocarditis (IE). These species express "Siglec-like" adhesins that bind sialylated glycans on host glycoproteins, which can aid the formation of infected platelet–fibrin thrombi (vegetations) on cardiac valve surfaces. We previously determined that the ability of S. gordonii to bind sialyl T-antigen (sTa) increased pathogenicity, relative to recognition of sialylated core 2 O -glycan structures, in an animal model of IE. However, it is unclear when and where the sTa structure is displayed, and which sTa-modified host factors promote valve colonization. In this study, we identified sialylated glycoproteins in the aortic valve vegetations and plasma of rat and rabbit models of this disease. Glycoproteins that display sTa vs. core 2 O -glycan structures were identified by using recombinant forms of the streptococcal Siglec-like adhesins for lectin blotting and affinity capture, and the O -linked glycans were profiled by mass spectrometry. Proteoglycan 4 (PRG4), also known as lubricin, was a major carrier of sTa in the infected vegetations. Moreover, plasma PRG4 levels were significantly higher in animals with damaged or infected valves, as compared with healthy animals. The combined results demonstrate that, in addition to platelet GPIbα, PRG4 is a highly sialylated mucin-like glycoprotein found in aortic valve vegetations and may contribute to the persistence of oral streptococci in this protected endovascular niche. Moreover, plasma PRG4 could serve as a biomarker for endocardial injury and infection.